2019
DOI: 10.3390/nano9040630
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in Li@Fullerenes and Li+@Fullerenes: First Principle Insights to Li-Based Endohedral Fullerenes

Abstract: This work reveals first principle results of the endohedral fullerenes made from neutral or charged single atomic lithium (Li or Li+) encapsulated in fullerenes with various cage sizes. According to the calculated binding energies, it is found that the encapsulation of a single lithium atom is energetically more favorable than that of lithium cation. Lithium, in both atomic and cationic forms, exhibits a clear tendency to depart from the center in large cages. Interaction effects dominate the whole encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 48 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…In the case of [Li @C ][PF ], the measured diffraction patterns were consistent with a positional disordering of the cation within a shell with a radius of about 1.5 [Å] at 155 [K] and the presence of two crystallographically equivalent positions of Li located 1.40 ± 0.01 [Å] from the cage center at 22 [K] [ 91 ]. These experimental findings are in agreement with the original HF/DZP prediction of the radial displacement amounting to 1.30 [Å] [ 45 ] and the displacements of 1.40, 1.43, and 1.50 [Å] subsequently computed at, respectively, the M06-2X/6-31G** [ 93 ], MN15/cc-pVTZ [ 86 ], and B3LYP/cc-pVTZ [ 94 ] levels of theory.…”
Section: Further Experimental Developmentssupporting
confidence: 87%
“…In the case of [Li @C ][PF ], the measured diffraction patterns were consistent with a positional disordering of the cation within a shell with a radius of about 1.5 [Å] at 155 [K] and the presence of two crystallographically equivalent positions of Li located 1.40 ± 0.01 [Å] from the cage center at 22 [K] [ 91 ]. These experimental findings are in agreement with the original HF/DZP prediction of the radial displacement amounting to 1.30 [Å] [ 45 ] and the displacements of 1.40, 1.43, and 1.50 [Å] subsequently computed at, respectively, the M06-2X/6-31G** [ 93 ], MN15/cc-pVTZ [ 86 ], and B3LYP/cc-pVTZ [ 94 ] levels of theory.…”
Section: Further Experimental Developmentssupporting
confidence: 87%
“…Bai et al. studied the encapsulation of Li + in various sizes of carbon cages and found the Δ E value for Li + @C 60 , Na + @C 60 and K + @C 60 to be −33.0 kcal/mol, −25.8 kcal/mol and −29.2 kcal/mol, respectively, using the DFT(M062X)/6‐31G** method [73] . Ramachandran et al.…”
Section: Resultsmentioning
confidence: 99%
“…[72] Bai et al studied the encapsulation of Li + in various sizes of carbon cages and found the ΔE value for Li + @C 60 , Na + @C 60 and K + @C 60 to be À 33.0 kcal/mol, À 25.8 kcal/ mol and À 29.2 kcal/mol, respectively, using the DFT(M062X)/6-31G** method. [73] Ramachandran et al reported the ΔE for the Li + @C 60 complex to be À 18.8 kcal/mol at the MP2/6-31G level of theory. [34] BSSE calculations were performed using counterpoise correction scheme proposed by Boys and Bernardi.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies reveal that M06-2X/6-31G** level of theory works well for endohedral fullerenes. 16,18,[22][23][24] Further, to assess the suitability of this level of theory for the present work, we have performed an extensive investigation of reaction of C 60 with 1,3 cyclohexadiene and compared it with the available experimental result. 16 A barrier of B11.2 kcal mol À1 was obtained for the reaction of C 60 with 1,3 cyclohexadiene at M06-2X/6-31G** level of theory.…”
Section: Methodsmentioning
confidence: 99%